Kazakhstan Develops Smart Cities Institutional Repositories as Backbones of Digital Kazakhstan - Yap, Joseph M.; Jangulova, Tolkyn (ICoASL 2019, New Delhi. Ane Books Pvt. Ltd., 2019)
As a young and developing city, Astana and its people are preparing their way to become a smart city. A smart city “improves the quality of life for its citizens through technological means” (Guerra, 2017). Kourtit, Nijkamp &Arribas (2012) define smart cities as highly productive cities as they perform to have highly educated people. This paper introduces the development of Institutional Repositories as possible technological component of a smart city. In Kazakhstan, the government is pushing towards providing better online access to its citizens. It is also embarking on digital library projects being spearheaded by the National Academic Library. With such projects being developed, how sufficient in terms of open- access information do the five largest cities of Kazakhstan have? State universities have their own institutional repository projects that may be a good inclusion to the smart city project. A survey of Astana University libraries and other four major cities was conducted to find out the number of existing Institutional Repositories that could possibly support the goal of the government to realize its full potential to be an innovative smart city...
Keywords: library; Institutional Repository